The influence of organizational culture on supply chain integration - Aćimović, Slobodan; Mijušković, Veljko; Todorović Spasenić, Ana (Serbian Journal of Management, 2021)
A team of employees that strives for the realization of a common goal is what every company needs, and the success of business depends on the way of functioning and thinking of that team. The organizational culture shapes the way employees think, react and behave. The business practice of companies in the Republic of Serbia has shown that the organizational culture oriented to employees, action and challenges is an important determinant of improving all business performance indicators, including the supply chain integration, which is the main topic of analysis within this paper. The dimensions of organizational culture affect internal integration, integration with customers and integration with suppliers, determining the generation of the key goal of supply chain management which refers to the delivery of the right product, at the right place, at the right time and at reasonable costs.